Multicolored Nanocolloidal Hydrogel Inks. (29th September 2021) - Morozova, Sofia M.; Statsenko, Tatiana G.; Ryabchenko, Egor O.; Gevorkian, Albert; Adibnia, Vahid; Lozhkin, Maksim S.; Kireynov, Alexey V.; Kumacheva, Eugenia
Abstract: Nanocolloidal gels are emerging as a promising class of materials with applications as inks in 2D and 3D printing. Polymer nanoparticles (NPs) offer many advantages as potential building blocks of nanocolloidal gels, due to the ability to control NP dimensions, charge, surface chemistry, and functionality; however, their applications as inks in printing are yet to be explored. Here, functional nanocolloidal hydrogels formed by percolating oppositely charged latex NPs with different dimensions and charge densities are reported. The shear‐thinning and self‐healing properties of the nanocolloidal gels and the mechanical properties of the resulting printed films are examined. NP functionality is achieved by covalently labeling them with different fluorescent dyes that emit at two distinct wavelengths. Using these NPs, a facile route for 3D printing of multicolored fluorescence patterns is shown, with each color being visualized under a specific, well‐defined excitation wavelength. Abstract : Nanocolloidal inks based on oppositely charged latex nanoparticles (NPs) are developed for 2D and 3D extrusion‐based printing. The inks exhibit shear‐thinning and self‐healing properties dependent on NP size and charge density. Inks formed by NPs labeled with distinct fluorescent dyes are used to print multicolor patterns.